Recruitment of older adults with type 2 diabetes into a community-based exercise and nutrition randomised controlled trial. Issue 1 (December 2016) - Miller, Eliza; Nowson, Caryl; Dunstan, David; Kerr, Deborah; Solah, Vicky; Menzies, David; Daly, Robin
Abstract Background Recruitment of participants into long-term community-based lifestyle intervention trials, particularly adults with a chronic disease, is often slow and challenging. Currently there is limited data on successful recruitment strategies suitable for older adults with type 2 diabetes into community-based exercise and nutrition programs, and no information on cost estimates associated with such recruitment. The aim of this report is to describe the recruitment strategies used and the success of each approach in recruiting older adults with type 2 diabetes into a 6-month community-based exercise and nutritional supplementation randomised controlled trial (RCT). A secondary aim is to assess the costs associated with the recruitment methods used. Methods The Resistance Exercise, Vitamin D and Muscle Protein Intervention Trial (REVAMP-IT) for type 2 diabetes is a 24-week RCT targeting 202 adults with type 2 diabetes which is designed to evaluate whether post-exercise ingestion of a whey- protein and vitamin D-enriched drink can enhance the effects of progressive resistance training (PRT) on glycaemic control, body composition and cardiometabolic health. Participants in this trial were randomly allocated to either: (1) theLift for Life ® community-based PRT program combined with additional whey protein and vitamin D, or (2) theLift for Life ® PRT program alone. Recruitment strategies included state and local newspaper and radio advertisements, targeted mail-outs, doctor and allied health referrals, community presentations, web-based media and word of mouth. The number of expressions of interest, participants screened and included in the trial, and how they first heard about the study were recorded by research staff during the screening process. Reasons for ineligibility or non-participation in the trial were also recorded as was the cost of each recruitment method used. Results A total of 1157 expressions of interest were received over a 21-month recruitment period. Overall 959 (83 %) individuals were screened and found to be ineligible for the trial or chose not to participate or could not be contacted further following their initial enquiry. As a result, 198 participants were randomised to the 24-week intervention. The most effective recruitment strategies were targeted mass mail-outs (39 % of the total participant sample), state (27 %) and local (14 %) print media. In total recruitment expenditure was AUD$40, 421, which equated to AUD$35 per enquiry and AUD$204 per eligible participant. Targeted mail-outs and state print media were the most expensive strategies each accounting for 38 % of total expenditure. Conclusions To recruit around 200 older adults with type 2 diabetes into a community-based lifestyle intervention trial in a timely manner, it is important to ensure that an adequate budget is allocated to recruitment as targeted mail-outs and state/local print media were the most costly but effective strategies. Trial registration Australian New Zealand Clinical Trials Registry referenceACTRN12613000592741 . Registered on 27 May 2013.